Economic Inclusion and Financial Integrity. - International Monetary Fund. Communications Department (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses various aspects of economic inclusion and financial integrity. The consecration of capitalism comes during the 19th century. With the industrial revolution came Karl Marx, who focused on the appropriation of the means of production-and who predicted that capitalism, in its excesses, carried the seeds of its own destruction, the accumulation of capital in the hands of a few, mostly focused on the accumulation of profits, leading to major conflicts and cyclical crises. Trust, opportunity, rewards for all within a market economy-allowing everyone's talents to flourish are the attributes of inclusive capitalism. The most recent poll conducted by the Edelman Trust Barometer, for example, showed that less than a fifth of those surveyed believed that governments or business leaders would tell the truth on an important issue. By making capitalism more inclusive, capitalism can be made more effective, and possibly more sustainable. However, if inclusive capitalism is not an oxymoron, it is not intuitive either, or it is more of a constant quest than a definitive destination.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Capitalism's Survival; Capitalism; Inclusive Capitalism; Private Ownership; SPE; United States